A Multi-Criteria Decision Analysis Approach for Managing End-of-Life Options of 3D Printing Thermoplastic - Nadhirah Tajurahim, Nurul Ainina; Tuan Mohammad Suzani, Tuan Nurin Nabila; Mahmood, Salwa; Ngadiman, Nor Hasrul Akhmal; Azit Kesumar, Mohammad Azwan (International Journal of Integrated Engineering, 2025)
The increasing use of 3D printing technology, particularly with thermoplastic materials, emphasizes the imperative for a meticulously devised strategy to address sustainability concerns at the end of the product’s life cycle. This study presents a customized Multi-Criteria Decision Analysis (MCDA) approach designed to navigate the intricate factors that affect the sustainable management of thermoplastic waste generated by 3D printing techniques. This framework provides decision-makers with a methodical paradigm to evaluate and prioritize end-of-life (EOL) modalities. It incorporates a wide range of variables, including resource consumption, environmental impact, economic implications, and statutory requirements. Based on the Analytic Hierarchy Process (AHP), the results of the algorithm clearly indicate that recycling is the best EOL option for the thermoplastic category studied in this analysis compared to other techniques. The utilization of MCDA enables stakeholders to make decisions that not only improve sustainability results but also drive innovation and efficiency within the 3D printing ecosystem.